If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + -1 = 2 + k Reorder the terms: -1 + 2k = 2 + k Solving -1 + 2k = 2 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. -1 + 2k + -1k = 2 + k + -1k Combine like terms: 2k + -1k = 1k -1 + 1k = 2 + k + -1k Combine like terms: k + -1k = 0 -1 + 1k = 2 + 0 -1 + 1k = 2 Add '1' to each side of the equation. -1 + 1 + 1k = 2 + 1 Combine like terms: -1 + 1 = 0 0 + 1k = 2 + 1 1k = 2 + 1 Combine like terms: 2 + 1 = 3 1k = 3 Divide each side by '1'. k = 3 Simplifying k = 3
| X^4+11=35 | | 18+7x-9=-27+3x | | -10=(1/4)(8y-12) | | -1x+0.33=0.25 | | 50b+36c= | | x+12=-(13) | | 50b+3c= | | 9+3(3x+5)=24+9x | | 50b+3= | | 60/p=4;15,16,17 | | 1/2x5/4 | | 2(14)-x+8=0 | | x/-7=(-5) | | -5x+13=-15 | | z+2=z | | 8b+10b+2+3b= | | s=6r^3(s/6r^3) | | -10+6x=3x-4 | | X/48=5/6 | | 7x+5=-5x | | 9(x+2)-7=2x+11 | | 0.25y=2/3-6 | | 1=-2x+16 | | 6.4*8.4=52.08 | | y=-2(1)+16 | | X^2+8y+2x-23=0 | | 0=-16t^2+128t+30 | | 8x-168=2x+562 | | 15+3(4-3x)=2x-6 | | 0.72a=14.25 | | X^2+42-32=0 | | 5-4j+j-1=-23 |